Peran Profitabilitas, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan - Muhamad Ridwan; Dul Muid (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of profitability, capital structure, and firm size on firm value in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Profitability is measured using Return on Assets (ROA), capital structure using the Debt to Equity Ratio (DER), firm size using total assets, and firm value using the Price to Book Value (PBV). The sample was selected through a purposive sampling method based on specific criteria, resulting in 160 firm observations. The study uses secondary data obtained from the companies’ annual financial reports published by the IDX. Data analysis was conducted using SPSS software, including descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that profitability has a positive and significant effect on firm value, meaning that companies with higher profitability tend to have higher firm value. Firm size also shows a positive and significant effect on firm value, suggesting that larger companies with greater total assets tend to achieve higher market valuation. However, capital structure does not have a significant effect on firm value, implying that the balance between debt and equity is not necessarily a key determinant of market value for companies in this sector.